Impact of carbon tax on energy generation transitioning technology - Lau, Benjin En Cheng (Nanyang Technological University, 2021)
The effect of carbon taxes on the optimum generation mix in Singapore's electrical grid is investigated using two statistical programming models. The first paradigm provides economic incentives for decommissioning of high-CO2 burning power plants and promotes investment in newer coal, wind, hydro, and, in some cases, nuclear power plants. The second model uses current generating assets after the investment of new gas, solar, wind, and nuclear capacity to optimise the power flow. A carbon tax encourages the early retirement of coal-fired power plants, which are replaced with low-emission gas, wind, and nuclear plants. It is only when the carbon tax exceeds $14/tCO2 that cleaner energy generation technology enters the system and makes an impact, although wind and solar should be displaced by nuclear power if that option is permitted. Despite its high initial costs, nuclear outperforms wind and solar, because wind needs to run in conjunction with gas generators, which is not needed for nuclear energy, and the cost-to-power ratio of solar panels is very poor. Although wind and solar have the potential to reduce CO2 emissions, their feasibility for Singapore is limited because of low energy densities and seasonal nature.